Interrelated factors influencing the human development potential in the Central region of Mongolia /For example Umnugovi province/ (Mongolian Journal of Geography and Geoecology, 2025)
This article examines the main factors of human potential formation. There is a gradual increase in the human development index in the Umnugovi region. This is due to the influence of various factors that are closely interrelated and have varying degrees of manifestation at the regional level. To assess the degree of influence of factors on human development, a selection of indicators characterizing the situation in the region was made. All indicators are aggregated into four groups of factors and given a total value in the range from zero to one, which allows for a quantitative assessment of the factors. This makes it possible to assess the degree of influence of a particular factor on human potential development, as well as to identify the main problems, the solution of which will contribute to further improvement of human development.